ESG Implementation And Sustainability In SME Sector In India - Dalua, Soumya Prakash (Digital Repository of Theses, 2025)
The integration of Environmental, Social, and Governance (ESG) practices has emerged as a vital driver of sustainable business performance, shaping corporate behavior and influencing investment decisions worldwide. While large corporations have increasingly adopted ESG frameworks, small and medium enterprises (SMEs), the backbone of the Indian economy, continue to face challenges in embedding such practices due to financial, technical, and regulatory constraints. This study investigates the extent of ESG implementation among Indian SMEs and its relationship with sustainability outcomes across environmental, social, and economic dimensions. Adopting a quantitative, survey-based methodology, data were collected from SME managers and decision-makers across diverse sectors and regions in India. The findings reveal that ESG adoption in SMEs remains limited and uneven, with governance practices relatively stronger than environmental and social initiatives. Nonetheless, SMEs that integrate ESG practices demonstrate improved operational efficiency, stakeholder trust, and resilience, underscoring ESG’s role as a strategic tool rather than a compliance burden. Key barriers identified include a lack of awareness, inadequate resources, and the absence of SME-specific reporting frameworks. This research contributes to stakeholder and institutional theory by contextualizing ESG adoption in emerging markets and provides actionable insights for policymakers, industry associations, and SMEs. By highlighting enablers and constraints, the study offers a roadmap for strengthening ESG integration in Indian SMEs, aligning with national sustainability commitments and global development goals.